2021
DOI: 10.1111/cid.12974
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implant in the posterior region combined with alveolar ridge preservation and sealing socket abutment: A retrospective 3D radiographic analysis

Abstract: Background Customized sealing socket abutment (SSA) has been claimed to optimize the peri‐implant hard and soft tissues in type 1 implant placement. However, the evidence to claim the benefits of this technique over the use a conventional healing abutment remains weak. Purpose The aim of this retrospective study was to provide a 3D‐radiographic evaluation of hard tissues changes following immediate implant placement in molar sites combined to ARP technique and installation of SSA. Materials and Methods Baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…This value was located within the normal range of bone resorption that is reported in the literature [29][30][31][32] . Similarly, in a retrospective study 3 , the authors reported stable vertical bone loss at all investigated implant surfaces following immediate implant placement in extraction sockets and replacement of socket sealing abutments. Also, Cheng et al 33 demonstrated a stable vertical bone dimension for immediate implant in posterior region when combined with bone grafting (deproteinized bovine bone mineral).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…This value was located within the normal range of bone resorption that is reported in the literature [29][30][31][32] . Similarly, in a retrospective study 3 , the authors reported stable vertical bone loss at all investigated implant surfaces following immediate implant placement in extraction sockets and replacement of socket sealing abutments. Also, Cheng et al 33 demonstrated a stable vertical bone dimension for immediate implant in posterior region when combined with bone grafting (deproteinized bovine bone mineral).…”
Section: Discussionmentioning
confidence: 75%
“…The use of CBCT in monitoring alveolar bone changes around the implants was advocated in several studies 7,22,27,28 . One year follow-up was used as it has been reported that most of bone remodeling occurred around immediately placed implants happened with the first year after implant insertion and no extensive bone loss occurred thereafter 3 . At all implant surfaces, vertical bone loss (P-BIC) did not exceed 1.2mm in the first year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IIP in the posterior mandible can provide faster recovery of masticatory function in selected scenarios [ 3 , 25 , 26 ]. However, surgeons need to try their best to prevent serious complications such as LPP.…”
Section: Discussionmentioning
confidence: 99%